(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study examines John Searle’s theory of speech acts as a stage representing methodological regulation in pragmatic studies. Through this framework, Searle reconstructed the theory on the basis that language is an organized form of action governed by rules, and that meaning is determined through the interaction of intention with conventions and context, rather than being an inherent property of words themselves. He grounded this view in a precise distinction between regulative rules that organize pre-existing linguistic behavior and constitutive rules that create new forms of linguistic action, maintaining that the realization of speech acts is conditioned by their conformity to foundational rules that operate implicitly, and that the illocutionary act constitutes the basic unit of linguistic communication. On the basis of the relationship between language and the world, the study presents the notion of directions of fit and adopts it as a point of departure for explaining the functional classification of speech acts proposed by Searle, which culminates in a fivefold taxonomy: assertives, directives, commissives, expressives, and declarations. The study highlights the distinctions among these categories in terms of illocutionary purpose, force, psychological state, context, and conditions of satisfaction. In light of this theoretical framework, the study further elucidates Searle’s distinction between direct speech acts, in which illocutionary force coincides with literal meaning, and indirect speech acts, whose meaning is inferred through contextual and inferential processes. This perspective reveals that language does not merely serve an informative function, but rather constitutes a complex communicative practice, the understanding of which depends on the interaction between linguistic structure, pragmatic intention, and social context.